Seasonality and function of Mesolithic valley-bottom sites: Results from Galgenbühel/Dos de la Forca, Adige valley (South Tyrol, Italian Alps). (22nd November 2016) - Wierer, Ursula; Betti, Lorenzo; Gala, Monica; Tagliacozzo, Antonio; Boscato, Paolo
Abstract: Seasonal mobility connected to a scheduled resource exploitation is a recurrent topic in the interpretation of the Early Mesolithic settlement pattern of the Adige Basin in the South Eastern Alps. Nevertheless direct archaeological seasonality data are scarce. This work presents new results from seasonal dating on faunal remains from the Sauveterrian site of Galgenbühel/Dos de la Forca in the Adige Valley (Northern Italy) frequented between 9265 ± 70 and 8454 ± 46 BP uncal. (8699–7459 BC cal.) by hunter–gatherer–fisher communities. An effort to collect and combine multifold data in order to dispose of complementary evidence for the interpretation, was made. Analyses are based on the incremental bone growth structures of the fish remains, tooth eruption/shedding and bone fusion of juvenile macromammals as well as on the presence of migrating birds. Results highlight a general preponderance of data referring to spring and summer throughout the stratigraphic sequence, whilst autumn–winter evidence is sporadic. The reasons for a marked spring–summer occupation of the site, best documented by the fish sample, partly the result of targeted catches, are most likely related to the predominant wetland economy. Seen in a regional perspective, the results break up with the dichotomy of "winter-valley bottom" and "summer-mountain territories" used to explain the relationship between low- and highland sites. A first comparative analysis between neighboring valley bottom rock-shelters based on macrofaunal ecology and economy as well as shelter exposition, suggests a higher variability in site function, and maybe also occupation season, as prospected so far.